Reallocation, Competition, and Productivity: Evidence from a Financial Liberalization Episode - Varela, Liliana (Review of Economic Studies, 2018)
This article studies the impact of distortions in the access to international capital markets on competition and productivity. I show that a reduction in these distortions leads to an increase in aggregate productivity through two different channels. First, firms that were previously credit constrained respond to better financing terms by increasing their investment in technology, a reallocation effect. Secondly, non-constrained firms also expand their investment in technology because of increased competition, a pro-competitive effect. I provide evidence for these two channels using firm-level census data from the deregulation of international financial flows in Hungary.